The influence of calculation method and relative strength on the load-velocity relationship in bench press exercise - Bautista, I. J.; Martin-Rivera, F.; Martinez, I.; Haff, G. G.; Maroto-Izquierdo, S. (International Journal of Sports Science & Coaching, 2022)
Purpose The objective of this study was: (1) to compare the effect of the calculation method using average (Avalue), and best value (Bvalue) of Mean Propulsive Velocity (MPV) on the Load Velocity Profile (LVprofile) during the barbell bench press exercise in elite handball players. In addition, (2) to analyze the relationship between the individual coefficient of variation (CVind) of an incremental load protocol in the bench press exercise with relative strength (Frel) in professional handball players.